Głos wołającego na pustyni. O Józefie Patkowskim w kontekście biografii "Ambasador muzyki z Marsa" Agnieszki Pindery - Atys, Szymon (Res Facta Nova, 2020)
The article is a review of book Patkowski. Ambassador of Music from Mars by Agnieszka Pindera, the first biography of Józef Patkowski, Polish musicologist, founder and longtime manager of the Polish Radio Experimental Studio. It contains a summary and evaluation of the book from a musicological perspective. Particular attention was paid to the previously unknown facts about Patkowski’s life established by the author. The text refers to the broad problems of the reception of electronic and avant-garde music in Poland and to the new wave of interest in the SEPR heritage.